2010
DOI: 10.1590/s0103-64402010000400003
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy analysis of RinsEndo system and conventional irrigation for debris removal

Abstract: A new device for irrigation, which presents hydrodynamic activation based on the pressure-suction technology, has recently been introduced to the market: the RinsEndo system. This study compared the efficacy of the RinsEndo system and conventional (manual-dynamic) irrigation in the removal of debris from the root canal walls, using scanning electron microscopy (SEM). Twenty mandibular premolars with completely formed roots were selected and randomly divided into group 1 (irrigation with the RinsEndo system) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 20 publications
3
14
1
3
Order By: Relevance
“…This result is in agreement with those of studies that used similar SEM analysis (Hü lsmann et al, 1997; Salman et al, 2010;Vivan et al, 2010) or optical microscopy (Ferreira et al, 2004;Fornari et al, 2010;Nadalin et al, 2009;Passarinho-Neto et al, 2006), and found debris in flattened areas of the canals that were not reached by the endodontic instruments. However, among the irrigation/activation protocols evaluated in the present study, those using ultrasonic and apical negative pressure irrigation (EndoVac system) were more effective for removal of debris.…”
Section: Microscopy Research and Techniquesupporting
confidence: 92%
“…This result is in agreement with those of studies that used similar SEM analysis (Hü lsmann et al, 1997; Salman et al, 2010;Vivan et al, 2010) or optical microscopy (Ferreira et al, 2004;Fornari et al, 2010;Nadalin et al, 2009;Passarinho-Neto et al, 2006), and found debris in flattened areas of the canals that were not reached by the endodontic instruments. However, among the irrigation/activation protocols evaluated in the present study, those using ultrasonic and apical negative pressure irrigation (EndoVac system) were more effective for removal of debris.…”
Section: Microscopy Research and Techniquesupporting
confidence: 92%
“…[35][36][37] In contrast, a comparison of the RinsEndo, a device for automatic irrigation, with conventional cleaning using a syringe found no significant difference in cleaning capability. 38) Dynamic cleaning has also been reported to increase the chemical permeability of dentin. 39) In the former, sodium hypochlorite solution and EDTA were used as the irrigants, whereas the irrigant solutions used in the latter, were sodium hypochlorite solution or …”
Section: Discussionmentioning
confidence: 99%
“…25 Yapılan başka bir araştırmada ise; kök kanallarındaki dentin debrisini uzaklaştırma etkinliği bakımından, RinsEndo ve konvensiyonel irrigasyon sistemleri arasında fark olmadığı bildirilmiştir. 48 EndoVac sistemi, endodontik irrigasyon yöntemlerinde, en son gelişim gösteren sistemlerden birisidir. Bu sistem sayesinde; kanaldaki tüm çalışma aralığının,sürekli gelen sıvı yardımı ile yıkanması sağlanır.…”
Section: Ardışık Düzenli Basınç Oluşturan Cihazlarunclassified